2016
DOI: 10.1002/anie.201509715
|View full text |Cite
|
Sign up to set email alerts
|

Solution Layer Deposition: A Technique for the Growth of Ultra‐Pure Manganese Oxides on Silica at Room Temperature

Abstract: With the ever increasing miniaturization in microelectronic devices, new deposition techniques are required to form high-purity metal oxide layers. Herein, we report a liquid route to specifically produce thin and conformal amorphous manganese oxide layers on silicon substrate, which can be transformed into a manganese silicate layer. The undesired insertion of carbon into the functional layers is avoided through a solution metal-organic chemistry approach named Solution Layer Deposition (SLD). The growth of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The MnSiO 3 barrier layer was deposited by a process developed in our team. 17 After Cu deposition, annealing was performed at 300°C during 3 h under a H 2 flow to stabilize the copper layer. After these steps, the substrate was used as the working electrode for the electrodeposition of thick copper layer.…”
Section: Experimental and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MnSiO 3 barrier layer was deposited by a process developed in our team. 17 After Cu deposition, annealing was performed at 300°C during 3 h under a H 2 flow to stabilize the copper layer. After these steps, the substrate was used as the working electrode for the electrodeposition of thick copper layer.…”
Section: Experimental and Materialsmentioning
confidence: 99%
“…Beyond the interest of this process for Cu layer deposition on silicon substrates comprising a copper diffusion barrier 17 (MnSiO 3 , see Experimental and Materials section), it has been employed on 3D silicon substrates presenting high aspect ratio structures like vias (depth and entry dimensions: 175−50 μm and 100−10 μm, aspect ratios of 3.5 and 10 respectively) or trenches (25−0.8 μm, aspect ratio of 31). Figure 8 presents cross section views of vias and trenches observed after ca.…”
Section: Application To 3d Silicon Fillingmentioning
confidence: 99%
See 1 more Smart Citation
“…While Cure et al recently showed the growth of manganese oxides at room temperature and partially in a liquid phase, this approach still required a dedicated synthesis of the metalorganic precursor (MnAmd2), the processing in anhydrous toluene, in neutral gas environment and utilization of oxygen plasma. 19 Similarly, some solution-based ALD processes were previously described for other oxides, such as TiO2 or MgO, but they were always limited by the need of controlled, neutral gas environment and partially anhydrous conditions. 20,21 In our approach, we avoided the challenges posed by the classical ALD processes by using aqueous solutions of common KMnO4 as the manganese precursor and a surface-adsorbing alcohol as the permanganate reducer (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Second, because the as-grown MnO 2 is also a catalyst for ozone decomposition, ALD of MnO 2 on nanostructured substrates with large surface area may be unfeasible, as suggested by the reports on this ALD process. ,, Furthermore, both the thermal- and plasma-ALD processes are vacuum techniques performed at elevated temperatures, requiring costly and reactive metal–organic precursors and a sophisticated, thermally isolated vacuum equipmentimplying a high processing cost. While Cure et al recently showed the growth of manganese oxides at room temperature and partially in a liquid phase, this approach still required a dedicated synthesis of the metal–organic precursor (MnAmd 2 ), the processing in anhydrous toluene, in neutral gas environment, and utilization of oxygen plasma . Similarly, some solution-based ALD processes were previously described for other oxides, such as TiO 2 or MgO, but they were always limited by the need of controlled, neutral gas environment, and partially anhydrous conditions. , …”
Section: Introductionmentioning
confidence: 99%